How Job Creativity Requirements Affects Employee Creativity: Evidence From a Across-Level Analysis - Ma, Yingshuang; Zhang, Haomin; Dai, Yi (Frontiers in Psychology, 2021)
Taking a Pygmalion perspective and adopting a multilevel theoretical framework, this study examined creative process engagement a cross-level mediator between job creativity requirement and employee creativity. In addition, it examined team knowledge sharing as a moderator of these relations. Data from 71 teams of 453 employee-supervisor pairs from three companies in China demonstrated that creative process engagement mediates the positive relationship between job creativity requirement and employee creativity. We also found that team knowledge sharing moderated the relationship among job creativity requirement, creative process engagement, and employee creativity. Theoretical and practical implications of this study are discussed.